Analisis Pola Jaringan Komunikasi Passobis di Kabupaten Sidrap - Asri, Masra; Nurhakki, Nurhakki (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2024)
Communication technology provides functions and dysfunctions for every action, such as cyber phishing crimes, one of which is online fraud sobis (social business) passobis (actor/perpetrator) which is rampant in Sidrap Regency (Sidenreng Rappang). This research aims to analyze the pattern of Edge network relations as well as the role of actors (Nodes). The research used a mixed-method approach to collect data through oral and written communication. Data analysis management techniques used are data reduction, presentation, and conclusion drawing. The results of the study revealed that the network relationship pattern (edge) of Passobis in Sidrap Regency is One mode by involving all, Directed which indicates that actors are senders, receivers and there are subjects and objects, and Symmetrical, which is a two-way relationship where two actors are jointly involved in the relationship.